Air Side Facilities Planning for Terminal 3 Juanda Airport, Surabaya - Primashantiand, Etza Nandira (Journal of Transportation Study Forum, 2024)
Juanda Airport experiences a very rapid increase in the number of passengers from year to year, this has an impact on the increase in aircraft movements which causes delays. To overcome this problem PT. Angkasa Pura I will develop Juanda airport by building Terminal 3 which is targeted to serve up to 75 million passengers. However, the construction of Terminal 3 needs to be equipped with detailed planning of airside facilities which include runway, exit taxiway, taxiway, and apron. This detailed planning will consider aircraft movements when the airport is fully operational to avoid delays. In planning the airside facilities at Terminal 3, air traffic movement data was collected from 2009 to 2016 to predict the planned target number of passengers. From the results of the analysis carried out, the number of passengers reaching this target occurred in 2031 with the number of aircraft movements per year being 414,727. The aircraft planned for this plan is the Boeing 737 Max 8 aircraft which is a new generation of Boeing 737-800 type aircraft, which is the aircraft with the maximum movement results in 2031. And aircraft movements during peak hours in 2031 will reach 61 movements/hour. This number of movements is obtained from a simulation of aircraft movements in the planning year. After calculating the runway capacity, it was found that 2 runways were needed to serve aircraft movements at Terminal 3 Juanda. The maximum runway capacity that can be generated with the composition of aircraft classes operating in Juanda is class B: 10%, C: 20%, and D: 70%. In planning this airside facility, it is also calculated that it can serve large aircraft such as the A380. So, the runway length is 3900 m with a runway width of 86 m including the runway shoulder. The dimensions of the taxiway are 30 m including a shoulder width of 15 m on each side. The location of the exit taxiway along 2770 is measured from both ends of the runway at an angle of 300, and the area of the apron with pier (finger) type is 1,000,000 m2.